Hubungan Perilaku Pola Hidup Sehat dengan Risiko Kejadian Stroke - Fransiska Anita Ekawati Rahayu Sa'pang; Mery Solon; Matilda Martha Paseno (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Controlling one of the non-communicable diseases, namely stroke, can be done by practicing a CERDIK healthy lifestyle which is one of the important keys in implementing a healthy life. The purpose of this study was to analyze the relationship between healthy lifestyle behavior and the risk of stroke. This type of research uses a quantitative design cross sectional study approach. The population in this study were adults and the elderly in the working area of the Mamasa Health Center, West Sulawesi with 60 respondents selected using non-probability sampling technique accidental sampling approach. This study used the Healthy Lifestyle questionnaire by conducting validity and reliability tests and also using a stroke risk screening questionnaire. This study was tested using SPSS version 25 using chi square and the results obtained p=0.001 which means there is a relationship between CERDIK healthy lifestyle and the risk of stroke. Therefore, it is very important for the community to apply CERDIK healthy lifestyle behaviors to prevent stroke events so as to avoid non-communicable diseases so that the quality of life increases and a healthy community is realized.